Performance of the W-B-N ternary diffusion barrier for Cu metallization - Lee, CW; Kim, YT; Lee, HS; Park, YK; Lee, TH; Chen, Q; Richardson, NV (KOREAN PHYSICAL SOC, 2001)
The thermal stability of rf magnetron sputtered tungsten boron nitride (W-B-N) thin films has been investigated as a diffusion barrier between Cu and Si during subsequent annealing at 550 - 900 degreesC. The boron and the nitrogen impurities in W-B-N thin films provide a stuffing effect that is very effective for preventing the fast diffusion of Cu atoms during the high-temperature annealing process. A resistivity is attainable by annealing the Cu/W-B-N/Si thin films between 3 and 58 Omega -cm from room temperature to 900 degreesC. X-ray diffraction, nomarski microscopy, and electrical property analysis show that the W-B-N barriers do not react with Si during an annealing in a N-2 ambient at 1000 degreesC for 30 min and prevent interdiffusion of Cu atoms at 800 - 850 degreesC for 30 min, which is the best result so far for the thermal stability of a diffusion barrier.
Keywords: NITRIDE THIN-FILM; THERMAL-STABILITY; TUNGSTEN; SILICON; INTERFACE